Electric field distribution in power cable with nano and micro filler with high and low permittivity - Wahdain, S. S.; Ludin, N. K.; Amir Izzani, Mohamed; Illias, H. A.; Mohd Jamil, Mohamad Kamarol (IEEE, 2021)
This paper shows a comprehensive comparison study between Nano components and Micro components for high voltage power lines insulation depends on polymers such as Polyethylene like Low-Density Polyethylene (LDPE) and Cross- Linked Polyethylene (XLPE). Potential incidence may happen in the power cable, which is space charge phenomena, increase in the electrical field and can lead to a breakdown in the insulator. More precisely depends on fillers' effect on electrical field distribution with different relative permittivity and size of the filler’s particle in the insulation cable. Furthermore, this review implicates ample discussion regarding the impact of two materials considered as a filler material with nanometer size (100nm = 0.0001mm) and micrometer size (100μm = 0.1mm) which is zinc oxide (ZnO), borosilicate (SiO2). The study goal is to determine the impact of filler size, type and distribution of particles into the polymer matrix on the electrical properties such as relative permittivity, electrical breakdown and the average of the electrical field added to the structure for Nano and Micro size with fillers and without fillers are analyzed. Finally, it was concluded that the size of fillers gives a huge effect on the reduction of electric field compared to the different types of material with different relative permittivity.